Skeletal muscle HSP70 expression is not associated with glycogen availability during recovery in elite endurance athletes. - Gejl, K.; Dalgaard, L.; Hvid, L. G.; Ørtenblad, N. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The 70-kDa heat shock protein (HSP70) is a ubiquitous molecular chaperone which is highly inducible by cellular stress such as exercise. HSP70 seems to be involved both in the acute cellular restoration following damaging exercise, and likely also in the long-term adaptations to training.